Legal education and legal education as the basis for the formation of anticorruption culture and anti-corruption consciousness (Journal of actual problems of jurisprudence, 2017)
The article is devoted to theoretical and legal analysis of legal education and legal education, formation of anticorruption culture and anti-corruption consciousness in the Republic of Kazakhstan. The most important direction in combating corruption is anti-corruption education, which, first of all, uses the means of legal education and propaganda. It should be noted that these areas in the implementation of legal education require coordinated efforts not only of state bodies and specially authorized persons and structures. An important role in legal education is played by all institutions of civil society, human rights organizations, and also by individual citizens, in some way connected with the process of legal socialization of the individual. The implementation of the legal educational is not limited to specific and practical measures that are associated only with the formation of legal knowledge. As a general direction, legal education is inextricably linked with the education of ethical, religious, cultural, psychological and other traditions. In their totality, these efforts contribute to strengthening the rule of law, legal order, enhancement of legal culture. Formation of negative perception of society to corruption and anti-corruption education of the population should be an integral part of moral and civic education, legal culture, awareness of their rights and obligations to society.Key words: legal education, legal education, legal culture, legal awareness, corruption, fighting corruption, measures to prevent corruption, causes of corruption.